Do anthropogenic factors affect the improvement of vegetation cover in resource-based region?. (20th October 2020) - Feng, Dingrao; Yang, Chen; Fu, Meichen; Wang, Jinman; Zhang, Min; Sun, Yiyu; Bao, Wenkai
Abstract: Vegetation plays a vital role in ecological systems and, therefore, changes in vegetation reflect the state of the ecological environment. Anthropogenic factors significantly impact vegetation cover. This study investigated variations in vegetation cover and the contribution of anthropogenic factors to these variations using the resourced-based region Shanxi Province as a case study. Theil-Sen median slope analysis and Mann-Kendall tests were used to analyze the vegetation cover change. A series of quantitative and qualitative techniques including spatial econometric modeling and residual analysis modeling were used to assess the effects of anthropogenic factors including ecological policies, urbanization, and coal mining. The results showed that overall, vegetation cover increased in the study area, but parts of the region experienced degradation. Ecological policies have been implemented in Shanxi Province to benefit vegetation cover and have resulted in large-scale human-induced greening. Urbanization had a more significant influence on vegetation cover than did natural factors. The extent of mining areas was not a decisive factor compared to natural factors; however, coal mining did create government revenue and drive economic development. In this manner, government policies could guide anthropogenic factors to create "win-win" scenarios for the environment and economic development. The results of this study promote a deeper understanding of the impact of anthropogenic factors on the ecological environment in resource-based regions. Highlights: Vegetation cover increased, but parts of the region underwent degradation. It presented human-induce greening in resource-based region, Shanxi Province. Ecological policies had significantly positive influence on vegetation cover. Urbanization had vital impact on vegetation cover while considering natural factors. Human activities give "win-win" scenarios for environment and economic development.